Trends in depression and anxiety prevalence by cancer status among US adults: analyses of the 2019-2022 National Health Interview Survey - Jonathan Lee; Michelle Lee; Ian Kim; Cynthia M Begay; Jennifer Unger (BMJ Open)
Objective To examine trends in the prevalence of depression and anxiety during the COVID-19 pandemic among US adult cancer patients and survivors (CPS) in comparison to those of non-CPS (NCPS).Methods and analysis National Health Interview Survey 2019–2022 data were analysed using spline logistic regression.Results A total of 115 664 participants completed the survey (mean age (SD), 52.8 (18.4) years; 54.3% female; 12.6% CPS). The age-adjusted prevalence of depression significantly increased from 26.53% in 2019 to 29.78% in 2022 among CPS, while that of anxiety increased from 24.02% in 2019 to 28.08% in 2022. Throughout the pandemic, there were consistently significant annual increases in the prevalence of both depression and anxiety with CPS experiencing significantly faster rates of increase compared with NCPS (average annual absolute increase 0.72% in NCPS vs 1.08% in CPS, p<0.01 for depression; 0.98% in NCPS vs 1.35% in CPS, p<0.01 for anxiety). Difficulty in social activity engagement emerged as the primary risk factor for both depression (adjusted OR (aOR), 7.38 (95% CI, 7.04 to 7.73), p<0.01) and anxiety disorders (aOR, 7.58 (95% CI, 7.23 to 7.95), p<0.01). Significant interactions were found between difficulty in social engagement and cancer status on the diagnoses of depression (aOR, 0.72 (95% CI, 0.63 to 0.83), p<0.01) and anxiety (aOR, 0.62 (95% CI, 0.55 to 0.70), p<0.01).Conclusions The notably higher prevalence and more rapid increase in rates of depression and anxiety disorders among CPS compared with NCPS underscore the disproportionate impact of the COVID-19 pandemic on CPS and the necessity of prioritising mental health support and interventions for this population.